Gate Tuning of Förster Resonance Energy Transfer in a Graphene - Quantum Dot FET Photo-Detector - Li, Ruifeng (Sci Rep, 2016)
Graphene photo-detectors functionalized by colloidal quantum dots (cQDs) have been demonstrated to show effective photo-detection. Although the transfer of charge carriers or energy from the cQDs to graphene is not sufficiently understood, it is clear that the mechanism and efficiency of the transfer depends on the morphology of the interface between cQDs and graphene, which is determined by the shell of the cQDs in combination with its ligands. Here, we present a study of a graphene field-effect transistor (FET), which is functionalized by long-ligand CdSe/ZnS core/shell cQDs. Time-resolved photo-luminescence from the cQDs as a function of the applied gate voltage has been investigated in order to probe transfer dynamics in this system. Thereby, a clear modification of the photo-luminescence lifetime has been observed, indicating a change of the decay channels. Furthermore, we provide responsivities under a Förster-like energy transfer model as a function of the gate voltage in support of our findings. The model shows that by applying a back-gate voltage to the photo-detector, the absorption can be tuned with respect to the photo-luminescence of the cQDs. This leads to a tunable energy transfer rate across the interface of the photo-detector, which offers an opportunity to optimize the photo-detection.